Analysis of Student Learning Motivation in Coastal Environment - Irma Octaviani; Ana Andriani (Proceedings Series on Social Sciences & Humanities, 2025)
Education is one of the key keys to creating and shaping superior human qualities. In Indonesia, the education of children in coastal environments generally faces the same problems, namely low levels of education and inadequate socio-economic life. This study aims to analyze the learning motivation of students in coastal environments, especially in SD Negeri Cilacap 08, South Cilacap District. The method used was qualitative with an ethnographic approach, involving six informants through interviews and observations. The results showed that students' learning motivation varied, with a significant influence from parental support and surrounding social conditions. Students with high motivation receive strong support from parents, while students with moderate and low motivation often experience a lack of sustained attention. An unsupportive education environment and lazy peer influence also contribute to low enthusiasm for learning. This research emphasizes the important role of parents and communities in creating a supportive educational environment to increase students' motivation in learning.